11 Long-term survival in patients with ST-elevation myocardial infarction treated with timely PCI, delayed PCI, or a pharmaco-invasive strategy. (6th October 2022) - Laffan, J; Foley, A; ,; ,; ,; McCreery, C; Kearney, P; Kiernan, T; Kennedy, M; Byrne, RA
Abstract : Background: Urgent revascularisation is important in patients with ST-elevation myocardial infarction (STEMI) and is associated with better outcomes. Guidelines suggest that for patients who are likely to be treated within 120 minutes of diagnosis, primary percutaneous coronary intervention (PPCI) should be the preferred treatment. Those for whom this is unlikely should be treated with a pharmaco-invasive strategy. We aimed to compare survival in patients treated with timely PPCI (within 120 mins), delayed PPCI (>120mins), or a pharmaco-invasive strategy (t-PA) amongst an Irish population. Methods: Patients were identified from the Irish national acute coronary syndrome (ACS) registry. Ethical approval and a consent declaration were obtained to access data. All-cause mortality was determined using multiple source surveillance using central death notification and publicly accessible online death notifications. Proximity from home address to the nearest PPCI centre was determined using Google Maps. Statistical analyses were performed using Stata. Results: 7, 486 STEMI patients were identified from January 2013 – March 2018. 6, 612 were included in the analysis. Minimum follow up was 3 years, median follow up was 5.5 years. 4, 040 received timely PPCI, 2, 162 delayed PPCI, 335 t-PA. Baseline characteristics are shown in table 1 . There was no difference in survival between the timely PPCI (84.7%) and t-PA groups (84.2%) (HR 0.93, 95%CI 0.71–1.25; Log-Rank p=0.62). There was increased mortality in the delayed PPCI (80.6%) in comparison with both timely PPCI (HR 1.5, 95%CI 1.16–1.49; Log-Rank p<0.000) and t-PA groups (HR 1.23, 95%CI 0.93–1.66; Log-Rank p=0.16), figure 1, 2 . Conclusion: Patients who were treated with a pharmaco-invasive strategy had lower all-cause mortality on long term follow up versus those who received PPCI outside of the target treatment window. Given the high proportion of patients who received delayed PPCI (33%), consideration should be given to expanding a pharmaco-invasive approach to patients who are unlikely to receive timely PPCI.